2018
DOI: 10.1016/j.socscimed.2018.09.063
|View full text |Cite
|
Sign up to set email alerts
|

Conversations about pictorial cigarette pack warnings: Theoretical mechanisms of influence

Abstract: Background: Social interactions are a key mechanism through which health communication campaigns influence behavior. Little research has examined how conversations about pictorial warnings motivate behavior. Purpose: We sought to establish whether and how smokers’ conversations explain the effect of pictorial warnings on quit attempts. Methods: US adult smokers (n=2,149) participated in a controlled trial that randomly assigned them to have their cigarette packs labeled with pictorial or text-only warnings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Our results are consistent with the conceptual framework and hypothesis 3 that a portion of the effect of exposure to the messages from the 3 intervention components was received and shared in mothers’ social networks, which in turn affected social norms and then practices. A similar effect has been studied in another type of intervention, where conversations about the warnings were a key mechanism through which pictorial warnings influenced smoking quit attempts (13). These results provide evidence to support that messages from interventions (e.g., IPC) and campaigns (e.g., MM or social mobilization) are filtered through social networks (12), which then spread information and translate messages into norms (13, 14), leading to changes in practices.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Our results are consistent with the conceptual framework and hypothesis 3 that a portion of the effect of exposure to the messages from the 3 intervention components was received and shared in mothers’ social networks, which in turn affected social norms and then practices. A similar effect has been studied in another type of intervention, where conversations about the warnings were a key mechanism through which pictorial warnings influenced smoking quit attempts (13). These results provide evidence to support that messages from interventions (e.g., IPC) and campaigns (e.g., MM or social mobilization) are filtered through social networks (12), which then spread information and translate messages into norms (13, 14), leading to changes in practices.…”
Section: Discussionmentioning
confidence: 82%
“…A similar effect has been studied in another type of intervention, where conversations about the warnings were a key mechanism through which pictorial warnings influenced smoking quit attempts (13). These results provide evidence to support that messages from interventions (e.g., IPC) and campaigns (e.g., MM or social mobilization) are filtered through social networks (12), which then spread information and translate messages into norms (13, 14), leading to changes in practices. The current study only measured social norms as reported by mothers and not by other members of their social network.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For example, preexisting attitudes towards a particular food, associations with the label from previous exposures, and current nutritional knowledge may affect the label's acceptance and perceived effectiveness. In addition, substantial literature has found that social norms-often measured by interpersonal communication and perceived social approval-exert a powerful influence on behavioral intentions [54,55]. Thus, labels that trigger conversation and that signal social disapproval are likely to be more effective.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…[34][35][36] We also assessed warnings' impacts on constructs from the University of North Carolina (UNC) Tobacco Warnings Model 37 (TWM), an empirically driven model explaining how cigarette and e-cigarette warnings influence behaviour change, because these outcomes are also good proxies for actual message effectiveness. [38][39][40][41] Finally, we examined smoking and vaping warnings' effects on discouragement and thinking about harms of the non-focal behaviour (eg, smoking warnings' impact on discouragement from vaping) to evaluate whether messages about one product spill over to affect perceptions of the other product.…”
Section: Original Researchmentioning
confidence: 99%